Multi-objective optimization of soil water-nitrogen management practice and seeding rate for sustainable soybean production on the Loess Plateau of China - Zhenqi Liao; Xiaohui Ding; Hongxin Zhang; Hui Zhang; Zhijun Li; Fucang Zhang; Junliang Fan (Agricultural Water Management)
Improved soil and crop management practices are essential for enhancing soybean production, but a comprehensive evaluation of agronomic performance, economic benefit and environmental sustainability associated with various soil and crop management practices is still missing. Field experiments were performed on soybean using a split-split plot design on the Loess Plateau of China in 2019 and 2020, with soil water management practice as the main plot (NM: flat cultivation; RF: ridge-furrow cultivation with film mulch; RW: ridge-furrow cultivation with film mulch and supplemental irrigation), nitrogen rate as the sub-plot (N30: 30 kg N ha−1 and N60: 60 kg N ha−1) and seeding rate as the sub-sub plot (D16: 160,000 plants ha−1 and D32: 320,000 plants ha−1). A multi-level multi-objective fuzzy comprehensive evaluation model was established for analysis. The results indicated that the soil water-nitrogen management practice and seeding rate (p < 0.01) as well as the interaction between nitrogen rate and seeding rate significantly (p < 0.01) affected the growth, photosynthetic capacity, grain yield and its components, seed quality, economic benefits and resource use efficiency of soybean. The RWN30D32 treatment achieved the highest ranking for multi-objective optimization in both growing seasons. Compared with the local management strategy (NMN60D16), RWN30D32 significantly (p < 0.05) increased the canopy photosynthetic capacity, biological yield, grain yield, seed protein yield, seed oil yield, net income, ratio of output over input costs, crop water productivity, partial factor productivity of nitrogen and radiation use efficiency by 22.8 %, 66.7 %, 35.9 %, 20.1 %, 23.9 %, 69.8 %, 28.4 %, 29.0 %, 171.8 % and 18.5 %, while it decreased the hundred-grain weight, number of pods, seed protein content, seed oil content, energy use efficiency and carbon productivity by 5.4 %, 34.2 %, 11.6 %, 8.8 %, 20.5 % and 69.0 %, respectively. In conclusion, the optimized management practice exhibited significant improvements agronomic performance, economic benefits and resources use efficiency, which was recommended for sustainable soybean production on the Loess Plateau of China.